Higher Education Governance and Policy Change in Western Europe International Challenges to Historical Institutions - Dobbins, Michael; Knill, Christoph; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book provides a comparative analysis of the impact of'soft Europeanization' on higher education governance in Western Europe. Using concrete indicators of policy change, it focuses on university reform in Italy, France, Germany and the UK to explore how historical legacies and transnational communication have impacted policy pathways.
Keywords: Science; Science; Science, general